Transformasi Crowdfonding Syariah Terhadap Model Pembiayaan dalam Sistem Perbankan Syariah Digital - sahid, aurora soula; Abdul Hamid (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2025)
This article is a literature review that aims to explore the transformation of Islamic crowdfunding as an alternative financing model within the digital Islamic banking system. Using a qualitative approach through literature analysis, the study identifies and analyzes various models of Islamic crowdfunding and their integration with financial technology (fintech) in compliance with Sharia principles. The findings suggest that Islamic crowdfunding offers an inclusive and efficient financing solution, particularly for micro, small, and medium enterprises (MSMEs), by providing a transparent, equitable, and interest-free mechanism. Digital transformation presents new opportunities for Islamic financial institutions to adopt crowdfunding platforms as part of innovative financing strategies. The study also highlights the importance of regulation and digital literacy as key supporting factors in developing a sustainable Islamic crowdfunding ecosystem.